Modelling customers’ satisfaction with educational services provided by higher education institutions - A. . Kolesnikov; I. . Lebedeva (Высшее образование в России)
The article considers a problem of modelling of customers’ satisfaction with educational services on the basis of the latent factors determining relations between subjective and objective characteristics of the quality of educational service. The three stages of forming of customers’ satisfaction are revealed in the analysis, reflecting the dynamics of interaction between customers and educational service providers. To describe the essence of this interaction theconcepts of elementary and compound educational services are introduced.The results of experimental exploration of the level of educational service satisfaction in general and according to certain characteristics of students from different universities are represented. The typical situations of satisfaction are revealed regarding different educational forms, stages and specialties.The structure of latent satisfaction factors obtained in the exploratory factorial analysis for different types of customers is analyzed, the models of cause-effect relations between themare considered. The factors are interpreted from the point of view of customers and education service providers regarding the search for acute trends of education service quality improvement.